2018
DOI: 10.1534/g3.118.200367
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Balancing Selection on Population Differentiation: A Study with HLA Genes

Abstract: Balancing selection is defined as a class of selective regimes that maintain polymorphism above what is expected under neutrality. Theory predicts that balancing selection reduces population differentiation, as measured by FST. However, balancing selection regimes in which different sets of alleles are maintained in different populations could increase population differentiation. To tackle the connection between balancing selection and population differentiation, we investigated population differentiation at t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 68 publications
6
31
0
Order By: Relevance
“…These results suggest that HLA loci show high levels of variation, deviations from neutrality-equilibrium and relatively high levels of population differentiation, even though under balancing selection. This scenario is consistent with that described by Brandt et al [ 47 ], in which populations of the same geographic region tend to show higher F ST values for HLA SNPs, while populations of distinct geographic regions have lower F ST values. Suggesting that local adaptation of HLA alleles may contribute to population differentiation on a regional scale, however, without erasing signatures of long-term balancing selection.…”
Section: Resultssupporting
confidence: 93%
“…These results suggest that HLA loci show high levels of variation, deviations from neutrality-equilibrium and relatively high levels of population differentiation, even though under balancing selection. This scenario is consistent with that described by Brandt et al [ 47 ], in which populations of the same geographic region tend to show higher F ST values for HLA SNPs, while populations of distinct geographic regions have lower F ST values. Suggesting that local adaptation of HLA alleles may contribute to population differentiation on a regional scale, however, without erasing signatures of long-term balancing selection.…”
Section: Resultssupporting
confidence: 93%
“…Signatures of low and high genetic differentiation between populations can be the result of purifying or positive selection. However, balancing selection, a mechanism that could maintain polymorphism above the expected genetic diversity, could also in part result in genetic differentiation ( Brandt et al, 2018 ). To account for balancing selection, we compared the pairwise genetic diversity (π) among populations and we could not find signatures of elevated genetic diversity within the investigated regions under strong selection.…”
Section: Resultsmentioning
confidence: 99%
“…We also found that adaptive F ST values were generally lower than neutral values for Washington herds (Fig. 6D), which is expected in cases of balancing selection, especially when populations experience similar selective pressures, such as pathogenmediated selective regimes (Aguilar et al 2004, Brandt et al 2018. We did not observe this pattern in British Columbia, likely as a result of a high proportion of Rocky Mountain ancestry in sampled animals from some herds alone (Figs.…”
Section: Discussionmentioning
confidence: 61%